Systematic Review and Meta-analysis of Admission Inflammatory Biomarkers for Evaluating Prognosis in Acute Type A Aortic Dissection - Shirley, Sarah; Maerivoet, Alana; Wright, Helen L.; Field, Mark; Madine, Jillian (AORTA, 2025)
Acute type A aortic dissection (ATAAD) is traumatic and life-threatening involving a split of the intima media along a variable length of the aorta from aortic root to aortic bifurcation. The pathology results in a local and systemic inflammatory process with elevated inflammatory markers observed at hospital admission. This systematic literature review aimed to compare the effectiveness of admission inflammatory markers in predicting adverse outcomes in postoperative ATAAD patients. Eligibility criteria included studies reporting postoperative outcomes or receiver operating characteristic results stratified by routine admission markers of inflammation in ATAAD patients. The study protocol was registered with PROSPERO (CRD42022366509). Following abstract and full-text screening, 79 studies were included in the analysis, with 39 included in the meta-analysis. Meta-analyses using random effects models of white blood cell count, neutrophil count, and neutrophil to lymphocyte ratio stratified by survival indicated that levels were significantly lower in survivors than nonsurvivors. The mean difference for white blood cell count was 1.51 (confidence interval [CI = 1.07, 1.95]), neutrophil count 1.50 [CI = 1.05, 1.95], and neutrophil to lymphocyte ratio 3.45 [CI = 2.50, 4.41]. Similarly, survivors had lower C-reactive protein levels than nonsurvivors (standardized mean difference = 0.5227 [CI = 0.1781, 0.8672]). Conversely, lymphocyte counts were higher in survivors than nonsurvivors (mean difference = −0.12 [CI = −0.18, −0.06]). All models had significant heterogeneity despite using random effects models, likely due to the multitude of presentations. Hierarchical summary receiver operating characteristic models were performed for neutrophil-to-lymphocyte ratio and C-reactive protein and showed similar sensitivity at detecting mortality in ATAAD patients for each fixed specificity. Data showed that deranged inflammatory markers are associated with poorer outcomes in ATAAD; however, none of these measures provide suitable prognostic markers alone. Continued development of multifactorial risk scores, including inflammatory markers and other factors, such as thrombotic measures, may enable clinically relevant prognostic tools and risk stratification.
Keywords: acute dissection; prognostic markers; inflammation